Microbial diagnosis of endophthalmitis using nanopore amplicon sequencing - Kang Il Jun; Baek-Lok Oh; Narae Kim; Joo Young Shin; Jangsup Moon (Elsevier, 2021)
Objectives: We investigated whether nanopore amplicon sequencing of aqueous humor was capable of rapid pathogen identification in infectious endophthalmitis. Methods: 5 cases of culture-positive bacterial endophthalmitis and 3 cases of fungal endophthalmitis (1 culture-positive and 2 presumed) were included. DNA was extracted from the aqueous humor and vitreous specimen, and PCR of bacterial rDNA (16S) and fungal rDNA (ITS1 and D1/2/3) was performed. Then, nanopore amplicon sequencing was performed for 2 h. The results of amplicon sequencing were compared to those of conventional culture studies. Results: In all cases, pathogens were identified by amplicon sequencing of aqueous humor specimens. In 3 cases of bacterial endophthalmitis, the identified microbes were confirmed by culture studies of both aqueous humor and vitreous specimens. In 2 cases of bacterial and 1 case of fungal endophthalmitis, the identified pathogens were confirmed only by culture studies of vitreous specimens. In all cases, amplicon sequencing identified pathogen in a shorter turnaround time than culture studies. In 2 cases with negative culture results, amplicon sequencing of aqueous humor identified fungal pathogens. Conclusions: Our data demonstrates the potential of amplicon nanopore sequencing using aqueous humor to enable rapid, sensitive and less invasive microbial diagnosis of endophthalmitis.